Complete Radiographic Healing and Related Factors in Juvenile Osteochondritis Dissecans of the Talus. Issue 7 (30th July 2018) - Gandhi, Jigar S.; Park, Kunbo; Talwar, Divya; Lawrence, John Todd R.
Objectives: Rates of healing following treatment of juvenile osteochondritis dissecans (OCD) of the talus remain scarce. Additionally, there is a paucity of research into the outcomes associated with the treatment of these lesions. The purpose of this study was to evaluate radiographic healing of talar dome OCDs in adolescents. Methods: This was a retrospective review of patients ≤18 years of age with talar OCD from a single pediatric institution within a 12-year period. Charts and radiographs were reviewed for demographics and clinical data, lesion's location and dimensions, and physeal status. The final radiologic healing was evaluated at 1-year follow-up. Complete and incomplete healing groups were compared using multivariable logistic regression models to examine the predictive effects for the independent variables. A nomogram was produced from the study sample to allow predictions to be made in individual patients. Results: Ninety-two lesions in 74 patients with mean age of 13.1 years (range 7.1 to 18.0 years) were analyzed. 60.8% of the patients were female. Thirty-three (41.8%) lesions were treated conservatively, and 59 (58.2%) were treated surgically (drilling, debridement, microfracture, bone grafting, or loose body removal). Thirty-nine (42.4%) lesions demonstrated complete healing. Patients with complete healing were younger ( p 0.032) and had lower BMIs ( p 0.006) compared to those with incomplete healing. In a multivariate regression model, the factors that correlated significantly were the age, BMI, Berndt and Harty's stage at presentation and type of treatment (observation vs. surgical). Location and dimension of the lesion, physeal status (open vs. closed), presenting symptoms, and type of surgical procedure showed no association with likelihood of healing. A nomogram was developed using the independent variables that correlated significantly with the likelihood of complete radiographic healing (Figure 1). Conclusion: Complete radiologic healing of juvenile OCDs was more likely in patients with younger age and lower BMI. Although the difference in outcome between various surgical treatment types was not statistically significant, initial management with surgery was more likely to result in a complete healing compared to observation alone. To our knowledge, this is the first time a nomogram predicting outcome in terms of complete radiographic healing has been developed for juvenile OCD lesions of the talus. Besides its potential role in treatment decision making process, this nomogram can be used to counsel patients and their families with regard to the prognosis for healing. Figure 1. Nomogram for predicting outcome of juvenile osteochondritis dissecans (OCDs) lesion of the talus. To use the nomogram, one should place a straight edge vertically so that it touches the designated variable on the axis for each predictor and then should record the value that each of predictor provides on the "Score". All of the recorded "points" are then summed, and this value is located on the "total score" line with a straight edge. A vertical line drawn down from the "total score" line to the "Prob" line will identify the probability that the patient will demonstrate healing or progression toward healing after 12 months of treatment.